ZLN005 Alleviates In Vivo and In Vitro Renal Fibrosis via PGC-1α-Mediated Mitochondrial Homeostasis - Pengfei Zhu; Haijian Ma; Shichao Cui; Xiqiao Zhou; Weilong Xu; Jiangyi Yu; Jingya Li (MDPI AG, 2022)
Currently, chronic kidney disease (CKD) is one of the most common diseases; it is also a serious threat to human health due to its high mortality, and its treatment is still a major clinical challenge. Mitochondrial dyshomeostasis plays an important role in the development of CKD. ZLN005 is a novel peroxisome-proliferator-activated receptor-γ coactivator-1α (PGC-1α) activator from our laboratory. To explore whether ZLN005 can protect against CKD in vivo and in vitro, a unilateral ureteral obstruction (UUO) model and TGF-β1-treated renal tubular epithelial cells (TECs), respectively, were used in this study. We found that ZLN005-administrated UUO mice showed less kidney damages than control mice, as indicated by the reduced expression of fibrotic biomarkers in the kidney of UUO mice. ZLN005 treatment also alleviated the TGF-β1-induced fibrotic phenotype and lipid accumulation in TECs. Our study demonstrated ZLN005 treatment improved mitochondrial homeostasis at least partially via the activation of PGC-1α, thus maintaining mitochondria function and energy homeostasis. In summary, ZLN005 treatment ameliorates UUO-induced renal fibrosis, providing conceptional support for mitochondria-targeting therapies for chronic kidney disease.